Karl Husa: From the Austrian borderlands to the Thai seaside: Appreciation on the occcasion of his 70th birthday - Einzenberger, Rainer; Trupp, Alexander * (Austrian Geographical Society, 2021)
It is not possible to do justice to an outstanding personality on just a few pages, an academic who shaped generations of students and worked on diverse fields in population and regional geography over decades, from the Austrian borderlands to the Thai seaside. Our perspective is necessarily selective and limited by our experience as (Diploma and PhD) students of Karl from 2000 to 2014, academic colleagues, and friends. We share a professional interest in Southeast Asia and human geography and have collaborated in teaching, organising fieldtrip excursions, research, and publishing.